Ear lobes as facial landmarks for determining the occlusal plane (Mustansiria Dental Journal, 2018)
Aim of the study: The aim of this study was to introduce ear lobes as alternative landmarks for the interpupillary line during orientation of the occlusal plane. Also, the other aim was to compare the ear lobes with the pupils of the eyes to verify that they were indifferent as anatomical landmarks.Method: The alternative landmarks, ear lobes, were presented and the method for orienting the occlusal plane with these landmarks was introduced. Digital pictures of 30 subjects, who participated in the study, were analyzed to compare the parallelism of the interpupillary line with the ear lobes.Results: The results of this study showed that the interpupillary line was parallel with the line drawn between both ear lobes for the same subject.Conclusion: The ear lobes were reliable and dependable alternative landmarks for the orientation of the occlusal plane and could be used with less effort than that of the conventional method utilizing the interpupillary line.